Analysis Contributor Inflation Group “ Volatile Food” from Sector Agriculture in Jambi Province - Laura Vantania Safitri; M. Ridwansyah; Rosmeli Rosmeli; Erni Achmad; Nurhayani Nurhayani; Zainul Bahri (International Journal of Economics and Management Research, 2025)
Inflation in Jambi Province is influenced by volatile food groups, the study aims to see the effect of food prices on inflation, as well as inflation predictions in Jambi Province, 2019-2023 period, data analysis techniques using panel data, exponential smoothing methods to see inflation predictions. The results show that there is a significant effect of the price of rice, red chili, cayenne pepper, and broiler chicken on inflation, the price of shallots does not have a significant effect on inflation. The predicted value uses the exponential smoothing method where inflation in Jambi Province in the next 1 year will increase . The implications of the Jambi Provincial Government's price control policy require cooperation with the central government to stabilize food prices, such as regulating strategic food stocks and providing subsidies for farmers in terms of raw materials that support food production.